Baldellia repens subsp. baetica Talavera & Casimiro-Soriguer, first record for the province of Cordoba (Andalusia, Spain) - Martínez Sagarra, Gloria; Devesa, Juan Antonio (Acta Botanica Malacitana, 2022)
During the review of the herbarium specimens of the genus Baldellia preserved at COFC, it was detected a specimen of Baldellia repens subsp. baetica Talavera & Casimiro-Soriguer collected in the northwest of the province of Cordoba (Spain). This is the first record of the subspecies for this territory.